2019
DOI: 10.3390/ijerph16081345
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Multiple Health Behaviour Recommendations: A Cross-Sectional Comparison between Female Cancer Survivors and Those with no Cancer History

Abstract: Lifestyle behaviours have an important role in preventing cancer, reducing treatment side effects, and improving survival and quality of life for cancer survivors. This study investigated adherence to multiple lifestyle behaviours among women with and without a cancer history. From the Australian Longitudinal Study on Women’s Health (ALSWH) surveys, 2407 cancer survivors and 3896 controls (cancer free population) were identified. Based on the World Cancer Research Fund/American Institute for Cancer Research (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Most participants surveyed belonged to the moderate-risk lifestyle class and adhered to some of the NCCN guidelines for multiple health behaviors, which contrasts with the previous literature [ 15 , 32 , 33 ]. A small study ( N = 66) of cancer survivors from a survivorship care clinic found that only 7.6% were adherent to all six NCCN multiple health behavior guidelines [ 32 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Most participants surveyed belonged to the moderate-risk lifestyle class and adhered to some of the NCCN guidelines for multiple health behaviors, which contrasts with the previous literature [ 15 , 32 , 33 ]. A small study ( N = 66) of cancer survivors from a survivorship care clinic found that only 7.6% were adherent to all six NCCN multiple health behavior guidelines [ 32 ].…”
Section: Discussionmentioning
confidence: 73%
“…Among the general population without a cancer diagnosis, it is well-established that males are more likely to report riskier health behaviors, such as smoking and drinking, compared to females [ 37 ]. However, sex differences in multiple health behavior change between males and females has yet to be explored thoroughly among cancer survivors [ 15 , 32 ]. Interpersonal relationships through marital status may also buffer against non-adherence through provision of social support for health behaviors [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is also evidence to suggest that cancer survivors are more likely to adopt healthy behaviors regarding tobacco use, alcohol consumption, and physical activity than people without a history of the disease (Frazelle & Friend, 2016;Park et al, 2015). Contrary to the results found by Tollosa et al (2019), these results are based on the fact that experiencing cancer can positively impact individuals' motivation to adopt risk-minimizing health behaviors (Park et al, 2015). As pointed out by one of the experts during the discussion, Seifert et al (2012) highlight motivation as a key mechanism for change and the development and maintenance of new behaviors.…”
Section: Discussionmentioning
confidence: 84%
“…When discussing health promotion areas, the experts, based on their experience with cancer patients, addressed the need for nursing interventions to prevent risky behaviors. Studies show a high prevalence of alcohol consumption, smoking, drug use, physical inactivity, and overweight among cancer survivors (Tollosa et al, 2019). Nevertheless, there is also evidence to suggest that cancer survivors are more likely to adopt healthy behaviors regarding tobacco use, alcohol consumption, and physical activity than people without a history of the disease (Frazelle & Friend, 2016;Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One intervention that has been effectively achieved to achieve slight improvements in quality of life is progressive resistance training [28]. However, maintaining adequate levels of physical activity, favoring the maintenance of high levels of quality of life, both in breast cancer survivors [28,29], and in other patient profiles [30][31][32][33], as well as in a healthy population [34,35] remains necessary.…”
Section: Increase In the Quality Of Lifementioning
confidence: 99%